THE EFFECTIVENESS OF GARLIC (Allium sativum L.) EXTRACT AS OVICIDE OF Aedes aegypti’s EGGS - Apga Repindo; Endah Setyaningrum; Syazili Mustofa; Betta Kurniawan (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Background: The World Health Organization (WHO) noted to date approximately 50 million cases of dengue fever are found every year. Prevention efforts of vector of dengue fever have been carried out, that is using synthetic insecticides which gives negative effect for population, so natural insecticide is needed. One of them using garlics that contains allicin, saponin and flavonoid that can inhbit hatchability of Aedes aegypti’s eggs. This research objective was to know if garlics extract effective as the ovicide of Aedes aegypti’s egg.Methods: This experimental studies, which used completely randomized design, was performed in November 2013 in Laboratory of Zoology, Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Lampung. Concentration of the extract used was 0%, 0,1%, 0,3%, 0,5%, 0,7% and 1% with 4 repetitions for each treatment. Furthermore, was laid 20 eggs in each treatment and repetition, so was gotten the total number of samples of 480 eggs. Then, was observed number of eggs that did not hatch every 6 hours for three days. Hypothesis test using one- way ANOVA test and post hoc Bonferroni analysis.Results: At the end of the study, hypothesis test of one-way ANOVA resulted p-value<0,001. The results showed a decrease in hatchability of eggs of Aedes aegypti at concentrations of 0,1%, 0,3%, 0,5%, 0,7% and 1% compared to the negative control. In the post hoc Bonferroni analysis was known effective concentration compared to controls (0%) was 1%. The higher the concentration of the extract on the inhibition of hatching eggs will be higher as well.Conclussion: Garlic extract effective as the ovicide of Aedes aegypti’s egg. [J Agromed Unila 2014; 1(1):16-21] Keywords: Aedes aegypti, Allium sativum L., ovicide.